INVENTARISASI DAN PEMETAAN POHON BUAH (EDIBLE FRUITS) ASLI KALIMANTAN DI KEBUN RAYA UNMUL SAMARINDA (KRUS) - Tri Furi Megawati , Legowo Kamarubayana dan Sri endayani (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2015)
Inventory and Mapping of Native Borneo Fruit Trees (Edible Fruits) at Botanic Gardens of Unmul Samarinda (KRUS). The purpose of this study was to determined the diversity of plants (flora), especially varieties of fruit trees that can be used for human consumption (edible fruits) native Borneo and map the presence of the trees, so it can be the basis management of Botanical Gardens of Unmul Samarinda (KRUS).Retrieval of data by purposive sampling, where the object of this study is the plants (flora), especially fruit trees that can be used for human consumption (edible fruit). Sampling sites using transect method by setting the transect line with the direction of the contour lines cut by considering the representation of the type of community that was observed. In this study using four transects vary in length, 920 m long transect A, B transect length of 1,380 m, 1,200 m long transect C and D transects 680 m long, with a width of each transect 20 m.The presence of fruit trees on four transects contained 18 observation sites by the number of individuals 194 types of trees, where there were 10 types of transects A number of individuals with 21 trees, Transect B there were 15 types of the number of individuals 90 trees, Transect C there were 10 types of the number of individuals 66 transect D tree and there were 4 types of the number of individuals 17 trees. Dominant fruit tree roots in the family Moraceae that is kind of applicability (Artocarpus elasticus), of the 194 fruit trees there are 95 trees recorded applicability (Artocarpus elasticus) while for the type comprising at least kind of Longan Forest (Dimocarpus longan), Kapul (Baccaurea macrocarpa), complexioned Forest (Lansium sp), Acid Payang (Mangifera shelf), Kedawung (Parkia roxburghii), Forest Petai (Parkia speciosa) and Wanyi (Mangifera caesia) each attended only one type of tree. Fruit tree profile includes the average diameter and average trees height. For the highest average diameter of 91.04 cm and total height of the highest average 40.00 m which is a type Kedawung (Parkia roxburghii), the smallest average diameter were 16.18 cm and an average tree height 14.70 m at the smallest Keledang types (Artocarpus longifolius). Dominance index value was highest fruit trees on the type of therapy, (Artocarpus elasticus) with a value were 0.23980 and the second highest score on the type Kalangkala (Litsea garciae Vidal) with a value were 0.01406. The highest similarity index values found in A and C transect community that is 0.70, while the second highest found in the community of transect A and B as well as B and C communities with a value were 0.64.